Malaysian Research Universities and their performance indicators. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
Research universities worldwide have become more central to their societies primarily because they represent the central knowledge resources in the societies (Fieldman, 1994; Singh and Allen, 2006; Walshok, 1996).